The Effect of Workload on Employee Performance with Work Stress as an Intervening Variable - Yuli, Trin Kamalia; Irawati, Sandra; Mu'ammal, Immanuel (Jurnal Manajemen Bisnis dan Kewirausahaan, 2023)
The purpose of this study was to determine the effect of workload on employee performance with work stress as an intervening variable at the Department of Trade Department of Malang City's Diskopindag. This research is explanatory research. The research population consisted of 30 employees at the Department of Industry and Trade Cooperatives of Malang City. Sampling using total sampling so that the entire population is used as a research sample of 30 employees. The data collection technique is a questionnaire. The data analysis technique used is path analysis with the Structural Equation Modeling (SEM) method which is operated using smartPLS 4.0. The results of the study prove that workload has a significant effect on employee performance, workload has a significant effect on work stress, work stress has a significant effect on employee performance and workload has a significant effect on employee performance with work stress as an intervening variable.